The research of diagnosing parameters of aerodrome lights net - Нерет, В. І.; Сущенко, О. А. (Proceedings of National Aviation University (archive), 2003)
The analysis of main diagnosing parameters, which used in exploitation of aerodrome lights net is made base on the normative documents and exploitation experience. The new approach to the technique of their tests concerning ground is offered